1992
DOI: 10.3354/meps090023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth, behavior and lipid concentrations of walleye pollock Theragra chalcogramma larvae fed lipid-enriched, lipid-deficient and field-collected prey

Abstract: While growth and survival of marine fish larvae In the sea may be dependent on prey type, size and concentration, nutr~t~onal quality of prey may also play an important role. This study investigates the relationships of lipld content of prey with growth, gas bladder size, sinking rate, behavior and survival for larval walleye pollock Theragra chalcogramma under controlled conditions in the laboratory. Larvae fed lipid-deficient brine shrimp Artemia spp. nauplii had reduced growth, gas bladder size and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…This ability exhibited by harpacticoids contrasts to that of calanoids, whose DHA content fluctuates dramatically in short periods of time as a result of phytoplankton composition (Davis & Olla 1992). Conversely, harpacticoid copepods, which typically inhabit detritus-rich environments where food is deficient in essential FA, do possess the ability to actively synthesize these compounds in significant quantities (Nanton & Castell 1998).…”
Section: Transfer Of Lc-pufa In the Lower Marine Food Webmentioning
confidence: 79%
See 1 more Smart Citation
“…This ability exhibited by harpacticoids contrasts to that of calanoids, whose DHA content fluctuates dramatically in short periods of time as a result of phytoplankton composition (Davis & Olla 1992). Conversely, harpacticoid copepods, which typically inhabit detritus-rich environments where food is deficient in essential FA, do possess the ability to actively synthesize these compounds in significant quantities (Nanton & Castell 1998).…”
Section: Transfer Of Lc-pufa In the Lower Marine Food Webmentioning
confidence: 79%
“…ARA could have been obtained from ω6 SC-FA, possibly from 18:2ω6, which was present in small amounts in the bacteria. The ability of cyclopoid and harpacticoid copepods to bioconvert FA and survive on poor diets has been suggested by several studies (Norsker & Støttrup 1994, Nanton & Castell 1998, Watanabe et al 1978.This ability exhibited by harpacticoids contrasts to that of calanoids, whose DHA content fluctuates dramatically in short periods of time as a result of phytoplankton composition (Davis & Olla 1992). Conversely, harpacticoid copepods, which typically inhabit detritus-rich environments where food is deficient in essential FA, do possess the ability to actively synthesize these compounds in significant quantities (Nanton & Castell 1998).…”
mentioning
confidence: 89%
“…However, this may not always be true. Davis and Olla (1992) demonstrated that the DHA content of wild copepods (Acartia) fluctuated dramatically within as short a period as 12 days in the same openocean area, suggesting that fish larvae may encounter DHA deficiency in natural waters.…”
Section: -4 Discussionmentioning
confidence: 99%
“…The rate of allocation to lipid versus protein is likely to be sensitive to a variety of environmental factors, such as diet (e.g. Davis and Olla 1992). Some conditions may promote the incremental fattening of individuals as they grow older and/or larger.…”
Section: Hyperallometric Scaling Of Components and Energymentioning
confidence: 99%